Coexisting spin and Rabi oscillations at intermediate time regimes in electron transport through a photon cavity - Gudmundsson, Vidar; Gestsson, Hallmann; Abdullah, Nzar Rauf; Tang, Chi-Shung; Manolescu, Andrei; Moldoveanu, Valeriu (Beilstein Journal of Nanotechnology, 2019)
In this work, we theoretically model the time-dependent transport through an asymmetric double quantum dot etched in a two-dimensional wire embedded in a far-infrared (FIR) photon cavity. For the transient and the intermediate time regimes, the current and the average photon number are calculated by solving a Markovian master equation in the dressed-states picture, with the Coulomb interaction also taken into account. We predict that in the presence of a transverse magnetic field the interdot Rabi oscillations appearing in the intermediate and transient regime coexist with slower non-equilibrium fluctuations in the occupation of states for opposite spin orientation. The interdot Rabi oscillation induces charge oscillations across the system and a phase difference between the transient source and drain currents. We point out a difference between the steady-state correlation functions in the Coulomb blocking and the photon-assisted transport regimes.
Keywords: electron transport; interactions; photon cavity; photon-dressed electron states; time dependent

(untitled) - Bruhat, L. E.; Viennot, J. J.; Dartiailh, M. C.; Desjardins, M. M.; Kontos, T.; Cottet, A. (Phys. Rev. X, 2016)

(untitled) - Delbecq, M. R.; Schmitt, V.; Parmentier, F. D.; Roch, N.; Viennot, J. J.; Fève, G.; Huard, B.; Mora, C.; Cottet, A.; Kontos, T. (Phys. Rev. Lett., 2011)

(untitled) - Liu, Y.-Y.; Stehlik, J.; Eichler, C.; Mi, X.; Hartke, T. R.; Gullans, M. J.; Taylor, J. M.; Petta, J. R. (Phys. Rev. Lett., 2017)

(untitled) - Stockklauser, A.; Scarlino, P.; Koski, J. V.; Gasparinetti, S.; Andersen, C. K.; Reichl, C.; Wegscheider, W.; Ihn, T.; Ensslin, K.; Wallraff, A. (Phys. Rev. X, 2017)

(untitled) - Frey, T.; Leek, P. J.; Beck, M.; Blais, A.; Ihn, T.; Ensslin, K.; Wallraff, A. (Phys. Rev. Lett., 2012)

(untitled) - Mi, X.; Cady, J. V.; Zajac, D. M.; Stehlik, J.; Edge, L. F.; Petta, J. R. (Appl. Phys. Lett., 2017)

(untitled) - Cirio, M.; De Liberato, S.; Lambert, N.; Nori, F. (Phys. Rev. Lett., 2016)

(untitled) - Yang, P.-Y.; Lin, C.-Y.; Zhang, W.-M. (Phys. Rev. B, 2015)

(untitled) - Gudmundsson, V.; Jonsson, T. H.; Bernodusson, M. L.; Abdullah, N. R.; Sitek, A.; Goan, H.-S.; Tang, C.-S.; Manolescu, A. (Ann. Phys. (Berlin, Ger.), 2016)

(untitled) - Hagenmüller, D.; Schachenmayer, J.; Schütz, S.; Genes, C.; Pupillo, G. (Phys. Rev. Lett., 2017)

(untitled) - Dinu, I. V.; Moldoveanu, V.; Gartner, P. (Phys. Rev. B, 2018)

(untitled) - Cottet, A.; Dartiailh, M. C.; Desjardins, M. M.; Cubaynes, T.; Contamin, L. C.; Delbecq, M.; Viennot, J. J.; Bruhat, L. E.; Douçot, B.; Kontos, T. (J. Phys.: Condens. Matter, 2017)

(untitled) - Gudmundsson, V.; Abdullah, N. R.; Sitek, A.; Goan, H.-S.; Tang, C.-S.; Manolescu, A. (Phys. Rev. B, 2017)

(untitled) - Khomitsky, D. V.; Gulyaev, L. V.; Sherman, E. Y. (Phys. Rev. B, 2012)

(untitled) - Gudmundsson, V.; Sitek, A.; Lin, P.-y.; Abdullah, N. R.; Tang, C.-S.; Manolescu, A. (ACS Photonics, 2015)

(untitled) - Gudmundsson, V.; Abdullah, N. R.; Sitek, A.; Goan, H.-S.; Tang, C.-S.; Manolescu, A. (Phys. Lett. A, 2018)

(untitled) - Gudmundsson, V.; Sitek, A.; Abdullah, N. R.; Tang, C.-S.; Manolescu, A. (Ann. Phys. (Berlin, Ger.), 2016)

(untitled) - Gudmundsson, V.; Gainar, C.; Tang, C.-S.; Moldoveanu, V.; Manolescu, A. (New J. Phys., 2009)

(untitled) - Moldoveanu, V.; Manolescu, A.; Gudmundsson, V. (New J. Phys., 2009)

(untitled) - Gudmundsson, V.; Jonasson, O.; Tang, C.-S.; Goan, H.-S.; Manolescu, A. (Phys. Rev. B, 2012)

(untitled) - Gudmundsson, V.; Lin, Y.-Y.; Tang, C.-S.; Moldoveanu, V.; Bardarson, J. H.; Manolescu, A. (Phys. Rev. B, 2005)

(untitled) - Nakajima, S. (Prog. Theor. Phys., 1958)

(untitled) - Zwanzig, R. (J. Chem. Phys., 1960)

(untitled) - Lax, M. (Phys. Rev., 1963)

(untitled) - Gardiner, C. W.; Collett, M. J. (Phys. Rev. A, 1985)

(untitled) - Beaudoin, F.; Gambetta, J. M.; Blais, A. (Phys. Rev. A, 2011)

(untitled) - De Liberato, S.; Gerace, D.; Carusotto, I.; Ciuti, C. (Phys. Rev. A, 2009)

(untitled) - Scala, M.; Militello, B.; Messina, A.; Piilo, J.; Maniscalco, S. (Phys. Rev. A, 2007)

(untitled) - Jonsson, T. H.; Manolescu, A.; Goan, H.-S.; Abdullah, N. R.; Sitek, A.; Tang, C.-S.; Gudmundsson, V. (Comput. Phys. Commun., 2017)

(untitled) - Hohenester, U. (Phys. Rev. B, 2010)

(untitled) - Santos, J. P.; Céleri, L. C.; Landi, G. T.; Paternostro, M. (arXiv, 2017)

(untitled) - Batalhao, T. B.; Gherardini, S.; Santos, J. P.; Landi, G. T.; Paternostro, M. (arXiv, 2018)

(untitled) - Baez, J. C. (arXiv, 2011)

(untitled) - Gudmundsson, V.; Jonasson, O.; Arnold, T.; Tang, C.-S.; Goan, H.-S.; Manolescu, A. (Fortschr. Phys., 2013)

(untitled) - Swain, S. (J. Phys. A: Math. Gen., 1981)

Quantum Optics - Walls, D. F.; Milburn, G. J. (Springer Berlin, 2008)

(untitled) - Goan, H.-S.; Chen, P.-W.; Jian, C.-C. (J. Chem. Phys., 2011)

(untitled) - Wiseman, H. M.; Milburn, G. J. (Phys. Rev. A, 1993)

(untitled) - Bi Sun, H.; Milburn, G. J. (Phys. Rev. B, 1999)

(untitled) - Goan, H.-S.; Milburn, G. J. (Phys. Rev. B, 2001)

(untitled) - Gudmundsson, V.; Abdulla, N. R.; Sitek, A.; Goan, H.-S.; Tang, C.-S.; Manolescu, A. (Ann. Phys. (Berlin, Ger.), 2018)